2018
DOI: 10.3390/molecules23081871
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Mitochondria-Targeted Plastoquinone in a Rat Model of Neonatal Hypoxic–Ischemic Brain Injury

Abstract: Neonatal hypoxia–ischemia is one of the main causes of mortality and disability of newborns. To study the mechanisms of neonatal brain cell damage, we used a model of neonatal hypoxia–ischemia in seven-day-old rats, by annealing of the common carotid artery with subsequent hypoxia of 8% oxygen. We demonstrate that neonatal hypoxia–ischemia causes mitochondrial dysfunction associated with high production of reactive oxygen species, which leads to oxidative stress. Targeted delivery of antioxidants to the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…We introduce the concept of neuroprotective effects of mitochondria-targeted plastoquinone (SkQR1), which is a conjugate of plastoquinone with decylrhodamine 19 [80]. Plastoquinone is a major quinone contained in chloroplasts and cyanobacteria and acts as an electron transfer carrier in the photosynthesis system and exerts antioxidant effects.…”
Section: Mitochondria-targeted Delivery Of Antioxidants Using the Tppmentioning
confidence: 99%
“…We introduce the concept of neuroprotective effects of mitochondria-targeted plastoquinone (SkQR1), which is a conjugate of plastoquinone with decylrhodamine 19 [80]. Plastoquinone is a major quinone contained in chloroplasts and cyanobacteria and acts as an electron transfer carrier in the photosynthesis system and exerts antioxidant effects.…”
Section: Mitochondria-targeted Delivery Of Antioxidants Using the Tppmentioning
confidence: 99%
“…Dispersion of the mitochondrial membrane potential plays an extremely important role in process of cell death or apoptosis [ 32 ]. It was reported that mitochondrial dysfunction in neurons is the major cause of hypoxia-induced brain damage, which was caused by the reduced mitochondrial transmembrane potential and elevated ROS generation [ 33 , 34 ]. Here, we found that hypoxia enhanced ROS generation and reduced the ΔΨm in PC12 cells, indicating that hypoxia induced mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzing early consequences of HI demonstrated that the mitochondria of hippocampus cells are impaired between 2 h and 18 h after the insult (Weis et al, 2012), and that some mitochondria developed a high degree of swelling at 3 h of reflow. The mitochondrial dysfunction is associated with high production of reactive oxygen species, which leads to oxidative stress; this makes the mitochondria a prime target of antioxidant neuroprotective strategies (Blomgren and Hagberg, 2006; Skulachev et al, 2018). In present study, both HI effects were prevented by coumestrol administered pre‐hypoxia, but not post‐hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of HI is complex and several mechanisms and pathways contribute for both early and delayed brain damage. The HI insult causes mitochondrial dysfunction characterized by mitochondrial swelling and exposure of permeability transition pores, associated with high production of reactive oxygen species (ROS), which leads to oxidative stress and consequent cell death (Jiang et al, 2019; Skulachev et al, 2018). Interestingly, the male neonate's brain is more susceptible to these effects, as compared to females, as well as to greater long‐term cognitive impairments (Hill and Fitch, 2012; Netto et al, 2017; Weis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%